Recommendation Of Compost OPEFB and Colchicine Concentration On Plant Beans Long Renek (Vigna unguiculata var. Sesquagpedalis) - Fathurrahman F; Sri Mulyani; Parlinggoman Sinaga (Politeknik Negeri Lampung., 2023)
The prospects promising in the cultivation of vegetables in the lowlands is still very promising with increasing demand for vegetables in the market. The study aims to determine the effect of long beans renek the interaction of oil palm empty fruit bunch (OPEFB) compost fertilizer and concentration of colchicine. Experiments using a completely randomized design (CRD) factorial with two factors and three replications. FIrst, compost OPEFB consists of 4 levels and the concentration of colchicine second factor consisted of 4 levels. In a single application of fertilizer and colchicine significantly affected stem diameter and the highest is OPEFB3 (10.93 mm) and the treatment of colchicine K3 (10.63 mm). The treatment compost OPEFB and colchicine significantly affect the weight of the leaves, the highest OPEFB3 (3:23 g) and colchicine K3 (2:55 g). The observation of compost OPEFB at harvest time OPEFB 2 (44.00 days) and colchicine K3 (43.92 days). Most pods compost treatment OPEFB3 (121.85) and colchicine K0 (111.42). The highest fruit weight in compost treatment OPEFB3 (1579.26 g) and colchicine K0 (1504.31 g). The concentration of chlorophyll b at the age of 15 days highest leaf on a combination T1K1 (14401.17 mg L-1) and the concentration of colchicine K0 (111.42 mg L-1 ). Compost OPEFB and colchicine significantly on chlorophyll b of young leaves (15 days).